Hyperfine structure of electronically-excited states of the 39K133Cs molecule. (13th June 2019) - Orbán, A; Xie, T; Vexiau, R; Dulieu, O; Bouloufa-Maafa, N
Abstract: The possibility to shield short-range dynamics between colliding particles of an ultracold gas with an optical field is controlled by the details of their long-range interactions. Using an asymptotic model presented in a previous work (Orbán et al 2015 Phys. Rev. A 92 032510), we determine the long-range interaction between an excited and a ground-state alkali-metal atom, including their hyperfine structure. As an example we focus on the bosonic pair 39 K( 4 p 2 P 1 / 2, 3 / 2 ) +  133 Cs( 6 s 2 S 1 / 2 ), which corresponds to the second dissociation limit of the KCs molecule above the ground state. Several excited electronic states are found repulsive at large interatomic distances, being thus promising candidates for optical shielding. The results reveal that the hyperfine coupling scheme is essentially different from the one described in (Orbán et al 2015 Phys. Rev. A 92 032510) for the states correlated to the 39 K( 4 s 2 S 1 / 2 ) +  133 Cs( 6 p 2 P 1 / 2, 3 / 2 ).